Haematological and Serum Biochemical Reference Values for Deoni Breed of Cattle in Karnataka - SRIPAD. K; SHIVAMURTHY WAKARE; GIRIDHARA P; BYREGOWDA S.M (International Journal of Pharma and Bio Sciences, 2018)
Deoni breed of cattle, is an important dual-purpose native breed of cattle in India, originated from Bidar district in Karnataka and adjoining Latur district of the state of Maharashtra. Present study was taken up in five taluks of Bidar district, to determine the normal reference values of haematological and serum biochemical parameters of Deoni breed of cattle in general and for different genders and age groups of animals. Fifty five apparently healthy Deoni animals were grouped based on sex into male and female groups and based on age into three age groups viz., 0-4 years, 4-8 years and 8-12 years. Blood samples with and without anticoagulant, were collected from these animals taking all aseptic precautions. Haematological parameters such as total erythrocyte count, total leukocyte count, haemoglobin, packed cell volume, total platelet count, mean corpuscular volume, mean corpuscular haemoglobin and mcorpuscular haemoglobin concentration were determined using Haematology analyzer. Serum biochemical parameters namely Calcium, Phosphorus, Magnesium, Total Protein, Albumin, Serum Creatinine, Blood Urea Nitrogen, Serum Glutamate Pyruvate Transaminase and Serum Glutamate Oxalate Transaminase were determined using biochemical analyzer and standard biochemical kits. Mean and standard error values for all the haematological and biochemical parameters were calculated for the study population and all the different groups and compared between male and female and different age groups by Students ‘t’ test and ANOVA. These values are set as reference values for Deoni cattle breed in general and for respective groups, which would serve as reference values for comparison of normal with various physiological, nutritional and deficiency conditions in the Deoni breed of cattle.